Utilization of Dynamic Business Models for Organic Chicken Manure Tablet Fertilizer - Syarifuddin Mabe Parenreng; Dwi Handayani; Aprisal Nur; Mutawakkil Samjas; Ilal Khairin Al Hafid; Fitriani .; M. Rizqal Putra Perdana; Eka Lukman; Bhintang Maharani; Fitriani Ramli (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
Sidrap Regency has a reputation as a rice granary and egg production center in South Sulawesi. Currently, the laying hen population reaches 4,940,118 with a daily production of around 100,000 egg racks. This large production volume also produces very high volumes of chicken feces waste. Currently, this waste simply accumulates around the coop without being processed, causing air pollution, disturbing the environment, and causing health problems. The partner in this community service is the EMAS Cooperative, which has many members from various business sectors. However, several livestock businesses within the EMAS Cooperative do not yet have a dynamic business model process that can effectively manage resources, respond to market changes, and ensure business sustainability. Therefore, an innovation is presented in the form of technology for processing chicken feces into solid organic fertilizer in tablet form with market value, accompanied by the development of a dynamic business model to support sustainable business management. This community service activity is carried out in four main stages: field observation, problem analysis and solution determination, tool design and manufacture, and implementation and mentoring. The implementation results showed that farmers gained knowledge and skills in processing chicken feces waste into organic fertilizer inJurnal Tepat (Teknologi Terapan Untuk Pengabdian Masyarakat), Volume 8, Nomor 2, Tahun 20252tablet form, while also being able to apply a dynamic business model in managing the EMAS Cooperative business in a more adaptive and sustainable manner. Furthermore, training effectiveness measurements also showed improvements in all indicators, with the highest achievement being technical knowledge at 91%, followed by practical skills at 71%, conceptual understanding at 41%, and attitude and motivation at 34%. Business planning skills increased by 27%, although lower than other indicators, still indicating positive development and requiring further mentoring. These findings confirm that community service activities not only produce waste management solutions but also strengthen the managerial capacity of farmers in supporting business sustainability.